Ultrasound-Guided Anterior Mediastinotomy: A Feasible Tool for Critical Lymphoma Patients - Cascone, Roberto (Healthcare (Basel), 2021)
A significant part of all neoplasms growing in anterior mediastinum are lymphomas (25%). Achieving a correct diagnosis and a clear definition of a lymphoma’s subtype is crucial for beginning chemotherapy as soon as possible. However, most patients present a large mediastinal mass that compresses vessels and airway, with serious cardiorespiratory repercussions. Therefore, having multiple tools available to biopsy the lesion without worsening morbidity becomes fundamental. Patients enrolled in this study were unfit for a surgical biopsy in general anesthesia and the need to begin chemotherapy as fast as possible prompted us to avoid percutaneous fine needle aspiration to prevent diagnostic failures. Our observational study included 13 consecutive patients with radiological findings of anterior mediastinal mass. Ultrasonography was performed directly in the theatre to mark the lesion and to localize vessels and vascularized neoplastic tissue. Open biopsy was carried out in spontaneous breathing with a laryngeal mask and with short-acting medications for a rapid anesthesia, performing an anterior mediastinotomy. The mean operative time was 33.4 ± 6.2 min and spontaneous respiration was maintained throughout the procedure. No complications were reported. All patients were discharged in the first or second postoperative day after a chest X-ray (1.38 ± 0.5 days). The diagnostic yield of this approach was 100%. With the addition of ultrasonography right before the procedure and with spontaneous breathing, anterior mediastinotomy still represents a useful tool in critical patients that could hardly tolerate a general anesthesia. The diagnostic yield is high, and the low postoperative morbidity allows a rapid onset of chemotherapy.